2014
DOI: 10.1111/jace.12995
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Templating with Mutually Miscible Solvents: A Simple Path to Hierarchical Porosity

Abstract: Abstract:Ice templating, a route where ice crystals are used to template macroporosity, has been used to process a variety of materials with one level of macropores. We demonstrate here a variant of ice templating based on the solidification of mutually miscible solvents. The solidification of different phases, each defined by their own size and morphology, provides a simple one-step processing route for materials with hierarchical porosity defined by up to three levels of macroporosity. These concepts are dem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…A variety of solvents have been used to date: water [8], camphene [9], tert-butyl alcohol (TBA) [10], naphthalene/camphor [11], dioxane [12], terpene [13], deep eutectic solvents [14], or carbon dioxide [15]. Various terms have been coined for the process: ice templating [16], freeze-casting [1], crystal-templating [17], directional freeze-drying [18], freeze-thaw [19] freeze gelation [20], ice-segregation-induced self-assembly [21], or thermally induced phase separation [22]. Frozen solvent templating [23] is probably the most generic.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of solvents have been used to date: water [8], camphene [9], tert-butyl alcohol (TBA) [10], naphthalene/camphor [11], dioxane [12], terpene [13], deep eutectic solvents [14], or carbon dioxide [15]. Various terms have been coined for the process: ice templating [16], freeze-casting [1], crystal-templating [17], directional freeze-drying [18], freeze-thaw [19] freeze gelation [20], ice-segregation-induced self-assembly [21], or thermally induced phase separation [22]. Frozen solvent templating [23] is probably the most generic.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Guizard et al, concluded that inclusion of TBA in aqueous yttria-stabilized zirconia (YSZ) slurries resulted in hierarchical porosity in structures not strictly lamellar in morphology. 15 The authors attributed these observations to the formation of TBA-water eutectic upon slurry solidification, their choice of alcohol concentration being the eutectic concentration.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that compressive strength was improved because of the increased connectivity between ceramic lamellae from the addition of alcohols, and noted that alcohol additives also resulted in denser ceramic walls. Finally, Guizard et al 15 concluded that inclusion of TBA in aqueous yttriastabilized zirconia (YSZ) slurries resulted in hierarchical porosity in structures not strictly lamellar in morphology. The authors attributed these observations to the formation of a TBA-water eutectic upon slurry solidification, their choice of alcohol concentration being the eutectic concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, this method would be simple, cost effective and have a low environmental impact in order to be industrially viable; freeze‐drying fulfills these criteria. Moreover, recent findings showed that it is possible to tailor macroporosity in the presence of small quantities of an organic solvent . In addition, freeze‐drying with the aid of organic solvents was also demonstrated to preserve mesopores in ceramics, synthetic polymers, and non‐gelling crystalline nano­fibrillated polysaccharides (e.g., cellulose, chitin) .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent fi ndings showed that it is possible to tailor macroporosity in the presence of small quantities of an organic solvent. [ 15 ] In addition, freeze-drying with the aid of organic solvents was also demonstrated to preserve mesopores in ceramics, synthetic polymers, and non-gelling crystalline nanofi brillated polysaccharides (e.g., cellulose, chitin). [16][17][18][19] To date, however, mesoporous aerogels from gelling polysaccharides have not been successfully prepared via freeze-drying.…”
Section: Introductionmentioning
confidence: 99%